The secret in the old attic - Keene, Carolyn (New York : Grosset & Dunlap, 1970)
Nancy Drew must use clues in a dead man's letters to find some unpublished musical manuscripts that will save an old man and his granddaughter from financial ruin.
A challenge -- Spooky mansion -- Bad news -- A startling figure -- A suspected thief -- Nancy's ruse -- Black widow -- The strange secret -- A blue bottle -- Dangerous adventure -- The mysterious letter -- A surprising discovery -- An unpleasant caller -- Warning -- Wallpaper clue -- Poetic hint -- The hidden room -- Trapped -- Deadly darkness -- Plotter nabbed.
710L
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Drew, Nancy -- (Fictitious character); Drew, Nancy -- (Fictitious character); Drew, Nancy -- (Fictitious character); Women detectives; Women detectives; Women detectives; Adventure and adventurers; Mystery and detective stories; Action and adventure fiction; Action and adventure fiction; Detective and mystery fiction; Detective and mystery fiction; Fiction; Fiction